2016
DOI: 10.36326/kjvs/2016/v7i24346
|View full text |Cite
|
Sign up to set email alerts
|

Detection of feline Parvovirus (FPV) from Cats infected with Enteritis Using rapid test and Polymerase Chain Reaction in Iraq

Abstract: Feline Parvovirus (FPV) had a substantial outcome on cats at various ages. This study considered being the first in Iraq focused on detection of the virus in cats with diarrhea at different age groups in some Iraqi provinces. The present study, involved a collectin of 84 fecal samples or intestinal fecal samples from an infected cats (stray and pet). These specimens were checked for detection of presence or absence the viral antigen. The checking procedure was included using the rapid antigen test kit (Anigen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…These findings are in agreement with Amoroso et al [16]; Radhy and Zenad, [19] and Bukar-Kolo et al [23]. This may be due to the virus spreading to healthy domestic cats through stray cats that are clinical or subclinical infected, as these cats shed the virus over extended periods of time or when they are on the move and looking for food [21,42]. Additionally, the majority of domestic cat owners maintain their cats' health by vaccinating them and keeping them away from stray cats [22].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings are in agreement with Amoroso et al [16]; Radhy and Zenad, [19] and Bukar-Kolo et al [23]. This may be due to the virus spreading to healthy domestic cats through stray cats that are clinical or subclinical infected, as these cats shed the virus over extended periods of time or when they are on the move and looking for food [21,42]. Additionally, the majority of domestic cat owners maintain their cats' health by vaccinating them and keeping them away from stray cats [22].…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed that the prevalence of FPV in cats was significantly higher in the Duhok and Sumel regions compared to the Zakho regions. This result is comparable to Abdel-Baky et al [18]; Radhy and Zenad, [19] and Al-Bayati, [21] they found that there is a different prevalence of FPV in cats in various regions of the same country. The difference in prevalence may be related to management practices, cat lifestyles, sampling size, and various climatic factors such as temperature, humidity, and rainfall [18,28,45].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations